Detection Brucella sp. Antibody in Sapera (Saanen í— Peranakan Etawa) Goat using Rose Bengal Test (RBT) Method in Siliragung Subdistrict Banyuwangi Regency - Putri, Lusi Rosita Sartono; Lamid, Mirni; Lokapirnasari, Widya Paramita; Saputro, Amung Logam; Wibawati, Prima Ayu; Prastiya, Ragil Angga (Universitas Airlangga, 2023)
This study detected the presence of Brucella sp. antibodies in Sapera goats in Siliragung sub-district, Banyuwangi District using serological tests. The screening test used in this study was the Rose Bengal Test (RBT). Brucellosis causes goats to experience abortion and disruptive of reproduction system. The method used in this research is purposive sampling method using the criteria of sapera goats that have never been vaccinated. Using the blood serum of Sapera goats taken at the Siliragung subdistrict farm, Banyuwangi. The results of the study did not show any samples that were considered positive for Brucellosis in the Rose Bengal Test. In this study, no Brucella sp. antibodies were found in Sapera goats in Siliragung sub-district, Banyuwangi District.